PENGARUH GAYA BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DI SMAN 1 MAJENE - Nur Alisa; Ana Muliana Musli; Aprisal Aprisal (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The purpose of this study was to determine the Influence of learning styles and learning independence on the mathematical problem-solving Ability of students in class XI MIPA SMA Negeri 1 Majene. This study is an ex-post facto causal study with a sample of 78 students, namely 39 students of class XI MIPA 1 and 39 students of class XI MIPA 3 SMA Negeri 1 Majene which were selected using cluster random sampling. Data collection techniques used three instruments, namely: (1) learning style questionnaire, (2) learning independence questionnaire, (3) problem solving ability test. Data analysis using descriptive analysis and inferential analysis. The results of descriptive analysis of the data show that: (1) Visual learning style is in good category, audiotorial learning style is in good category, kinesthetic learning style is in good category (2) Learning independence is in very high category (3) Mathematical problem-solving ability students are in the sufficient category. The results of hypothesis testing using simple linear regression analysis and multiple linear regression, namely: (1) learning style has a significant effect on students' mathematical problem-solving ability, (2) learning independence has a significant effect on students' mathematical problem-solving abilities, (3) learning styles and independence learning has a significant effect on students' mathematical problem-solving ability